QUALITY OF LIFE ASSESSMENT OF INDIVIDUALS WITH WELL-DIFFERENTIATED THYROID CARCINOMA USING WHOQOL-100 - Fernanda de Oliveira Furino; Vanessa de Oliveira Furino; Débora Gusmão Melo; Lucimar Retto da Silva de Avó; Victor Hugo Maion; Carla Maria Ramos Germano (Cogitare Enfermagem, 2017)
This study aimed to assess the quality of life of patients under clinical monitoring due to well-differentiated thyroid carcinoma using the WHOQOL-100 questionnaire. A quantitative, descriptive and cross-sectional study was undertaken between March 2015 and March 2017 in São Carlos, SP, Brazil, evaluating 280 individuals, being 70 suffering from thyroid carcinoma and 210 controls, divided in ≤45 and >45 years. The results showed that the group with thyroid carcinoma ≤ 45 years presented impairments in the physical domain (p=0.0032) and in the level of independence (p<0.0001), and improvements in the environment domain (0.0138). The group with thyroid carcinoma > 45 years presented improvements in the environment domain (0.0002) and in the global quality of life (p=0.00146) in relation to the controls. These findings, resulting from a comprehensive analysis of the quality of life of patients with differentiated thyroid carcinoma, can contribute to the understanding of the repercussions the disease and its treatment entail.